Cu(I)-Catalyzed Cross-Coupling Rearrangements of Terminal Alkynes with Tropylium Tetrafluoroborate: Facile Access to Barbaralyl-Substituted Allenyl Acid Esters and 7‑Alkynyl Cycloheptatrienes - Fan, Zhe; Ni, Shao-Fei; Pang, Jin-Yu; Guo, Li-Ting; Yang, Hao; Li, Ke; Ma, Cheng; Liu, Ji-Kai; Wu, Bin; Yang, Jin-Ming (Journal of organic chemistry, 2022)
Herein, we report a novel strategy for the formation of copper carbene via the cycloisomerization of the π-alkyne–Cu(I) complex from terminal alkynes and tropylium tetrafluoroborate. Mechanistic studies and DFT calculations indicate that the reaction undergoes the intramolecular cycloisomerization process from the π-alkyne–Cu(I) complex to afford the copper carbene intermediate, followed by migratory insertion with the second terminal alkyne to afford the barbaralyl-substituted allenyl acid esters. In addition, we develop a mild and highly efficient Cu(I)-catalyzed cross-coupling protocol to synthesize 7-alkynyl cycloheptatrienes that has a broad functional group tolerance and is applicable to the late-stage functionalization of natural products.